Knowledge and Attitude of Adolescents on Reproductive Health (Rh): A Case of Padmakanya Higher Secondary School, Kathmandu - Paudyal, Narayan Prasad; Paudyal, Shivaraj (The Geographic Base, 2020)
The present study aims at finding out the essential knowledge and attitude on reproductive health among adolescents studying at the higher secondary level. It is a case study of Padmakanya H.S.S. of the total 110 girl students of class 11 and 12 were selected. This study is quantitative in design and descriptive in nature. A structured questionnaire was prepared for the collection of data in which 38 types of closed questions were asked to fulfill the objectives. The findings of the study reveal that irrespective of caste, religion, and ethnicity majority of the respondents have knowledge on reproductive health. About 90% of respondents have knowledge of it. Similarly, their attitude to have the knowledge of RH was entirely positive. Almost 91.8% answered positively for having its knowledge. They have the knowledge of family planning methods, birth spacing, appropriate age of marriage, and HIV/AIDS. They have acquired the required knowledge of components of RH such as infertility, safe motherhood, transmission and prevention of STIs and HIV, physical change, and menstruation cycle. However, some of them lack the knowledge of RH matter. Overall, the acquisition of knowledge of RH, the national birth rate, mortality, morbidity, and fertility is maintained at the national level.